Generating Purchase Intentions Through Live Streaming and Social Influence: Brand Trust as a Mediator - Jovita Damayanti Tjipto; Keni Keni (Jurnal Komunikasi, 2025)
The current surge in the beauty industry is attributed, in part, to the public’s growing awareness of the importance of maintaining skin health. This is reinforced by the observation that people tend to show a heightened interest in skincare products that are both affordable and of high quality. However, this boon has created various competitions and challenges for skincare industry companies. One such challenge is the societal perception of men using skincare products. Additionally, intense industry competition strengthens the competitiveness of companies. Recently, one highly effective marketing strategy that can enhance consumer purchasing intent and trust is live streaming through e-commerce. This provides companies with the convenience of reaching a broader consumer base. Meanwhile, after obtaining information through live streaming, consumers reinforce this information with various recommendations obtained from their surroundings. Therefore, this research aims to identify the influence of live streaming in e-commerce and social influence on purchase intention, as well as to analyze the mediating role of brand trust. Research hypotheses are tested using Partial Least Square – Structural Equation Modeling (PLS-SEM) with the assistance of Smart-PLS 4 software. Based on the results, it is revealed that one hypothesis is rejected, which pertains to the influence of live streaming in e-commerce on purchase intention. On other hand, social influence and brand trust successfully exert positive and significant influences on purchase intention. Furthermore, live streaming e-commerce and social influence significantly impact brand trust, and brand trust acts as a mediator between live streaming in e-commerce, social influence, and purchase intention.